Why Urban Ecology Matters in Ethiopia - Perry, Gad; Gebresenbet, Fikirte; DaPra, Michelle; Branco, Patricia; Whibesilassie, Wondmagegne; Jelacic, Matthew; Eyob, Abel Estifanos (Frontiers in Ecology and Evolution, 2022)
Three concurrent global environmental trends are particularly apparent: human population growth, urbanization, and climate change. Especially in countries such as Ethiopia in the Global South, all three are impacted by, and in turn have bearing upon, social justice and equity. Combined, these spatial and social factors reduce wellbeing, leading to increasing urgency to create urban environments that are more livable, resilient, and adaptive. However, the impacts on, and of, non-human urban residents, particularly on the ecosystem services they provide, are often neglected. We review the literature using the One Health theoretical framework and focusing on Ethiopia as a case-study. We argue for specific urban strategies that benefit humans and also have spillover effects that benefit other species, and vice versa. For example, urban trees provide shade, clean the air, help combat climate change, create more livable neighborhoods, and offer habitat for many species. Similarly, urban neighborhoods that attract wildlife have characteristics that also make them more desirable for humans, resulting in improved health outcomes, higher livability, and enhanced real-estate values. After summarizing the present state of knowledge about urban ecology, we emphasize components relevant to the developing world in general and pre- COVID-19 pandemic Ethiopia in particular, then expand the discussion to include social justice and equity concerns in the built environment. Prior to the ongoing civil war, Ethiopia was beginning to invest in more sustainable urbanization and serve as a model. Especially in light of the conflict and pandemic, much more will need to be done.